The Effect Of Using Taboo Games On The Interest In Learning Arabic Of Students In Class X MA Luqman Al-Hakim Limboto - Abdurahman, Isra; Damhuri; Abdullah (Al-Kalim : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
The interest in learning among students, particularly in Arabic language classes, can be influenced by monotonous learning environments and the lack of media used during classroom instruction. This research aims to determine whether the use of taboo games as a medium affects the interest in learning Arabic among 10th-grade students at Madrasah Aliyah Luqman Al-Hakim Limboto. In this study, the researcher employed a pre-experimental design with a one-group pretest-posttest format and utilized questionnaires for data collection. The sample consisted of all 12 students in the 10th grade at Madrasah Aliyah Luqman Al-Hakim Limboto. Based on the data analysis results, it can be concluded that the use of taboo games has an influence on the students' interest in Arabic language subjects. This is evidenced by the paired sample t-test results, where the significance value (2-tailed) is less than 0.05, indicating a significant impact of taboo games on students' interest in learning Arabic.  This research can serve as a recommendation for teachers to use taboo games as a medium in teaching Arabic. The use of taboo games can be an effective tool to motivate students and increase their interest in learning Arabic, making the learning process more enjoyable and interactive.